(untitled) (Qawanin Jurnal Ilmu Hukum, 2021)
A concept related to the concept of legal obligation is the concept of legal responsibility. A person who is responsible for certain legal actions that he or she can receive sanctions in case his actions are against the law. This research was conducted to see and analyze changes in the agreement and legal responsibility of SPBU Entrepreneurs towards PT. Pertamina in distributing fuel oil in Bantaeng Regency, as well as to see and analyze legal efforts that can be made by one of the parties that defaults on the cooperation agreement for the distribution of fuel oil in Bantaeng Regency. To answer the problem formulation in this research, empirical legal research methods are used. how to interview, document, and search for literature studies. To analyze the data, the writer used a descriptive method which was analyzed qualitatively. Based on the results of the study showed the cooperation agreement between PT. Pertamina and PT. Nur Aulia Pratama Karya in the form of a CODO gas station entrepreneur is implemented with a profit sharing system, where Pertamina will place its equipment at the gas station owned by PT. Nur Aulia Pratama Karya, then the gas station bought fuel from PT. Pertamina and distribute it to the public where the profit margin is divided between PT. Pertamina and PT. Nur Aulia Pratama Karya. The form of a written Cooperation agreement signed by both parties. The agreement was underhanded because it was not carried out in the presence of an angry official. Legal remedies made by one of the parties who defaulted on the agreement were regulated through deliberation, there was no agreement, so a legal route was reached at the Makassar District Court. Recommendations for this research So that the parties to the BBM distribution agency agreement can be made in the form of an official deed that can be trusted, such as a notary, so that the dispute situation in court can be used as perfect evidence. In order for the settlement of disputes even though there are clauses for settlement through the Court that are not successful through deliberation, it is also necessary to make efforts to include other dispute resolutions through non-litigation institutions.